2020
DOI: 10.3390/biom10060906
|View full text |Cite
|
Sign up to set email alerts
|

1H Nuclear Magnetic Resonance of Pig Seminal Plasma Reveals Intra-Ejaculate Variation in Metabolites

Abstract: In pigs, ejaculate is expelled in fractions, mainly the sperm-rich fraction (SRF) and the post-SRF (PSRF), which differ in both sperm content and origin. In addition, intra-ejaculate variability between fractions in terms of sperm reproductive characteristics has been previously reported, the highest sperm quality being observed in the first 10 mL of the SRF (SRF-P1). As seminal plasma (SP) composition has been purported to influence sperm physiology, the aim of this study was to profile pig SP metabolite comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 80 publications
2
5
0
Order By: Relevance
“…The present work identified and quantified a total of 23 metabolites in pig SP, including amino acids, saccharides, salts, alcohols, and other compounds. Compared to our previous work (Mateo-Otero et al, 2020), the present study quantified SPmetabolites, as well as identified new molecules (i.e., formate, fumarate, hypotaurine, isoleucine, malonate, myo-inositol, and trimethylamine N-oxide). These new findings may result from improvements in sample handling and purification, and the higher frequency and resolution of the NMR spectrometer.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The present work identified and quantified a total of 23 metabolites in pig SP, including amino acids, saccharides, salts, alcohols, and other compounds. Compared to our previous work (Mateo-Otero et al, 2020), the present study quantified SPmetabolites, as well as identified new molecules (i.e., formate, fumarate, hypotaurine, isoleucine, malonate, myo-inositol, and trimethylamine N-oxide). These new findings may result from improvements in sample handling and purification, and the higher frequency and resolution of the NMR spectrometer.…”
Section: Discussionmentioning
confidence: 85%
“…The NMR spectroscopy is one of the most used technologies in this field, because it provides a non-biased uniform detection of equal sensibility for all proton-containing molecules in samples, and requires little or no processing (Goodacre et al, 2004;Emwas et al, 2019). This analytical method has been widely used for SP-metabolite profiling of several mammalian species, including humans (Hamamah et al, 1993;Segalen et al, 1995;Gupta et al, 2011;Jayaraman et al, 2014;Bonechi et al, 2015;Mumcu et al, 2020), cattle (Kumar et al, 2015) and pigs (Kalic et al, 1997;Mateo-Otero et al, 2020). The present work identified and quantified a total of 23 metabolites in pig SP, including amino acids, saccharides, salts, alcohols, and other compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three fractions/portions can be objectively collected with clear differences in the SP source: (a) the first 10 mL of the so-called sperm rich fraction (SRF-P1), rich in sperm and with SP mainly originating from the epididymis; (b) the rest of SRF (SRF-P2), also rich in sperm and with SP mainly coming from the prostate ( Rodríguez-Martínez et al, 2005 , 2009 ), and, (c) the post-SRF (PSRF), poor in sperm and with SP mainly arising from the seminal vesicles ( Einarsson, 1971 ; Rodríguez-Martínez et al, 2005 , 2009 ; Saravia et al, 2009 ; Rodríguez-Martínez et al, 2011 ). Interestingly, the SP from these ejaculate portions has also been found to vary in terms of proteomic, metabolomic, and antioxidant capacity ( Saravia et al, 2009 ; Rodríguez-Martínez et al, 2011 ; Barranco et al, 2015 , 2016 , 2017 ; Perez-Patiño et al, 2016 ; Mateo-Otero et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Markers for sperm dysfunction [ 218 ] and (in)fertility have been detected in spermatozoa [ 27 , 190 , 219 , 220 ] and in the SP [ 221 , 222 ] of many species, including humans [ 218 , 222 , 223 , 224 , 225 ] and livestock [ 70 , 226 ]. They vary from gene presence [ 227 ], markers of Sertoli cell function [ 228 ], proteins [ 36 , 229 , 230 , 231 ], anti-oxidative enzymes [ 223 , 232 , 233 ] and metabolites [ 234 , 235 , 236 ] to exosome-associated molecules [ 237 , 238 ] and microRNAs [ 181 , 239 , 240 , 241 ].…”
Section: What Else Can Be Done With Our Current Knowledge Of Sp?mentioning
confidence: 99%